1992
DOI: 10.1007/bf00004482
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between gill chloride cell morphology and calcium uptake in freshwater teleosts

Abstract: The involvement of the freshwater fish gill chloride cells (CCs) in trans-branchial calcium uptake (JinCa(2+)) was investigated. This was accomplished by assessing the interspecific relationships between the apical surface area of CCs exposed to the external environment and JinCa(2+). Three species of freshwater teleosts, the rainbow trout (Oncorhynchus mykiss), the American eel (Anguilla rostrata) and the brown bullhead catfish (Ictalurus nebulosus), were used. Chronic (ten-day) treatment with cortisol in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 31 publications
1
42
0
2
Order By: Relevance
“…In killifish gills, seawater-type chloride cells have an apical pit and interdigitate with neighboring accessory cells to form multicellular complexes, whereas the apical membrane is flat or protrusive with developed microvilli on it in freshwater-type cells (Katoh et al, 2001). A similar apical membrane structure has been observed in several species adapted to freshwater (Hossler et al, 1985;Laurent and Hebibi, 1988;Perry et al, 1992;Shawn et al, 1993;Greco et al, 1996;Perry, 1997Perry, , 1998Kelly et al, 1999). …”
Section: Discussionmentioning
confidence: 74%
“…In killifish gills, seawater-type chloride cells have an apical pit and interdigitate with neighboring accessory cells to form multicellular complexes, whereas the apical membrane is flat or protrusive with developed microvilli on it in freshwater-type cells (Katoh et al, 2001). A similar apical membrane structure has been observed in several species adapted to freshwater (Hossler et al, 1985;Laurent and Hebibi, 1988;Perry et al, 1992;Shawn et al, 1993;Greco et al, 1996;Perry, 1997Perry, , 1998Kelly et al, 1999). …”
Section: Discussionmentioning
confidence: 74%
“…It is puzzling that the changes in ionocyte SA were not accompanied by similar changes in NKA activities, and clearly this result begs the question as to which metric is a better indicator of branchial ion transport capacity. Given the tight correlation between ionocyte SA and ionic uptake in freshwater teleosts (Perry et al, 1992a;Perry et al, 1992b) and the reports of a lack of correspondence between NKA activities and ionocyte abundance (McCormick, 1995;Sloman et al, 2001), the more reliable indicator would seem to be ionocyte SA. The fact that Cl -uptake did not significantly increase with increasing ionocyte SA in the present study suggests that one or more other factors (including NKA activity) are regulating this process in the fish experiencing gill remodeling.…”
Section: The Distribution and Putative Functions Of Ionocytes In Fishmentioning
confidence: 99%
“…On the basis of these and other indirect or correlative studies (18,26,28,32), a model was constructed (27) in which the MRC was implicated as the principal (potentially exclusive) cell type responsible for Ca 2ϩ uptake. In the present study, however, immunocytochemical analysis of gill cross sections in fish exposed to soft water failed to demonstrate strong colocalization of Na ϩ /K ϩ -ATPase (representative of MRCs) and ECaC-positive cells (Fig.…”
Section: Low Environmental Camentioning
confidence: 99%
“…It has been suggested that fish ECaC and TRPV subfamilies diverged prior to a possible gene duplication giving rise to TRPV5 and TRPV6 (35). Although the site of Ca 2ϩ uptake in freshwater fish is believed to be the chloride cell (also termed mitochondria-rich cell, MRC) (18,23,24,27,28,32), ECaC appears to be ubiquitously expressed in all of the gill epithelial cell types, including pavement cells (PVCs) and chloride cells (35).…”
mentioning
confidence: 99%